Bitcoin em Pagamentos Online: Expandindo a moeda digital em pagamentos digitais - Santos, Rute Costa (2022)
Technology has evolved exponentially, which has boosted the digitalization of payment systems. Thus, cryptocurrency emerged as a form of digital money and payment, whose adoption has been rising in recent years. On the other hand, the internet and technology also impacted e-commerce, which has potential for growth and development, consequently influencing online payment methods. While cryptocurrencies can attract and retain customers by offering an innovative, low-cost, and efficient payment alternative, there is still some resistance to market entry due to a lack of knowledge and trust. Aiming toward expanding the knowledge of cryptocurrencies, and sharing how payments with them work, this project seeks to develop a prototype capable of processing online Bitcoin cryptocurrency transactions. This prototype performs the integration with cryptocurrency payment gateways, being easily adapted to be integrated with other applications and support more cryptocurrencies. The evaluation conducted in this project is based on the Goal/Question/Metric approach, structuring the analysis concerning the quality attributes of Maintainability, Security and Reliability. The results are positive as the solution met all the expected values.